Baseline Factors Predictive of the Receipt of Second-Line Chemotherapy After Nab-Paclitaxel Plus Gemcitabine for Patients With Advanced Pancreatic Cancer. Issue 3 (March 2022) - Iede, Kiyotsugu; Yamada, Terumasa; Koh, Masahiro; Ueda, Masami; Tsuda, Yujiro; Nakashima, Shinsuke; Ohta, Katsuya; Tanida, Tsukasa; Matsuyama, Jin; Ikenaga, Masakazu; Tominaga, Shusei
Abstract : Objective: Second-line (2L) chemotherapy is important for improved survival in patients with advanced pancreatic cancer (APC). However, approximately half of patients with APC do not receive 2L chemotherapy because of disease progression or adverse events. Baseline factors predictive of the receipt of 2L chemotherapy remain unknown. Therefore, we investigated predictive factors for the receipt of 2L chemotherapy in patients with APC. Methods: Between January 2015 and March 2020, 53 patients with APC received nab-paclitaxel plus gemcitabine (AG) as first-line chemotherapy at our institute. Of these 53 patients, 29 patients received 2L chemotherapy, and 23 patients received best supportive care. Patients' characteristics were compared retrospectively, and predictive factors for the receipt of 2L chemotherapy were evaluated. Results: Sarcopenia and hypoalbuminemia at baseline were independent negative predictive factors for the receipt of 2L chemotherapy in multivariate analysis. Although the presence of sarcopenia did not affect the relative dose intensity through 8 weeks of AG therapy, patients with hypoalbuminemia had a significantly lower relative dose intensity. Conclusions: Sarcopenia and hypoalbuminemia at baseline might be negative predictive factors for the receipt of 2L chemotherapy after AG treatment in patients with APC.